Association Between Obesity and Falls Among Korean Adults: A Population-Based Cross-Sectional Study. Issue 12 (March 2016) - Kim, So Young; Kim, Min-Su; Sim, Songyong; Park, Bumjung; Choi, Hyo Geun
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The objective of this study was to evaluate the association between falls and obesity using Asian body mass index (BMI) classifications. Using the data from the Korean community health survey in 2011, a total of 229, 226 participants ranging from 19 to 106 years old were included in this study. The BMI groups were classified as underweight (<18.5), healthy (18.5 ≤ BMI < 23), overweight (23 ≤ BMI <25), and obese (≥25) using Asian BMI classifications. The associations between BMI groups and falls (≥1 time or ≥2 times per year) were analyzed using multiple logistic regression analyses with complex sampling. A subgroup analysis was conducted according to age (19–40, 41–60, and ≥61 years) and the location of the fall (indoor and outdoor). Physical activity, household income, education level, alcohol consumption, smoking, stress level, and medical comorbidities were adjusted as confounders. In total, 16.8% and 6.1% of the participants experienced falls ≥1 time and ≥2 times per year, respectively. Compared to the healthy weight group, the other BMI groups showed a significant U-shaped relationship with falls ≥1 time (AOR underweight = 1.12, 95% CI [confidence interval] = 1.05–1.19; AOR obese = 1.06, 95% CI = 1.02–1.10, P  < 0.001) and ≥2 times (AOR underweight = 1.14, 95% CI = 1.04–1.26; AOR obese = 1.04, 95% CI = 0.99–1.10, P  < 0.001). Obese status was significantly associated with falls (≥1 fall per year) in all age groups, whereas being underweight was significantly associated with falls in the 19 to 40 year age group only. In conclusion, both underweight and obese statuses were significantly associated with falls in this adult Korean population. However, the relationship between BMI group and falls varied according to age and the location of the falls.